RUMAH BACA HARAPAN: âSATU BUKU SEJUTA IMPIANâ - Setiawan, Ari; Khoirullah, Evi Miftahul; Rini, Indah Kusuma; Hakim, Lukman; Diasti, Rian (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
In 2011 around 31.05 million of Indonesian children dropped out from the school and most of them were living in small and isolated island. Pahawang island located in Pesawaran District is one of islands in Lampung province that has a low level of education. Therefore weâve initiative to built a reading house Rubah (Rumah Baca Harapan). The aims of this program were to collect both new and old books, create foster-sister program, youth and student empowerment, and create an ideal learning and education model in island. This program may able to be a model of non-formal education around islands of Indonesian archipelago.